Correlation of Serum Free Carnitine with Serum Ferritin and Vitamin C Levels in Type II Diabetic Men - Ahmad Pourabbas; Farnoush Fallah; Reza Mahdavi; Akbar Aliasgarzadeh (Tehran University of Medical Sciences, 2013)
Background: Diabetes is a major health problem worldwide. Type II diabetic patients are reported to have higher ferritin and lower vitamin C concentrations. Considering the role of ascorbic acid in carnitine biosynthesis and the limited information on free carnitine correlations with ferritin and vitamin C levels in diabetic patients without microvascular complications, this case-control study was conducted to determine ferritin and vitamin C levels in hyperlipidemic-diabetic men comparing to healthy controls; the correlation of free carnitine with ferritin and vitamin C levels were also studied in these patients.Methods: Thirty-five hyperlipidemic-diabetic and seventy healthy men, were included in the study by the convenience sampling method. Body Mass Index, blood pressure, fasting blood glucose, lipid profile, ferritin and vitamin C levels were assessed in both case and control groups; moreover, serum free carnitine was measured in both groups. Dietary assessments were performed using 24 hour recall and food frequency questionnaires.Results: Blood pressure, fasting blood glucose, cholesterol, triglyceride, LDL, and HDL concentrations were significantly higher in the case group. Mean serum ferritin concentrations were higher in diabetics comparing to controls (93.22±0.27 vs. 44.66±4.23 µg/l); whereas, mean plasma vitamin C in these patients were lower than the healthy subjects (0.68±0.07 vs. 0.89±0.05). Positive correlations were observed between free carnitine and vitamin C levels.Conclusion: According to the results, it could be suggested that vitamin C supplementation in diabetic patients with hyperlipidemia might be useful. In addition, inclusion of serum ferritin assay in routine evaluation of diabetic patients could be beneficial.